A review of Paracricotopus (Brundin, 1947), with the description of two new species and redescription of the adult males of Paracricotopus niger (Kieffer, 1913) and Paracricotopus uliginosus (Brundin, 1947) sensu Sæther (1980) (Chironomidae: Diptera) - Namayandeh, Armin; Ghaderi, Edris (Zootaxa, 2025)
In this study, we present a review of Paracricotopus species with emphasis on the characteristics of the adult male and provide other previously unknown and/or unexamined characteristics, particularly those of tergite setation. We also described two new species, Paracricotopus sturae sp. nov. and Paracricotopus torbjorni sp. nov., from Norway, redescribed P. niger and P. uliginosus, provided an updated key to the adult males and a preliminary alternative key based on adult males tergite setation.